Impacto económico de la calidad de la semilla en el cultivo de maíz (Zea May) en la cuenca alta del Río Guayas. - Merizalde Vélez, Diana Carolina (2010)
This research was conducted during 2010 in the cantons Quevedo, Buena Fe, Valencia and Mocache in Los Ríos province. Pursued the following objectives: calculate productive indexes about materials used in corn cultivation according seed used, analyze economic yield according quality seed used in corn cultivation and observe and diagnose factors social and economics by which farmers use a kind of seed. To this study was applied probabilism sampling simple aleatory, for this was taken a representative sample of all farmers from object zone study. The question nary used for the study included the next variables:................................................ .